The Relationship between Key Financial Indicators and Bank Performance: A Case Study of 10 Major Indonesian Commercial Banks - Lin, Yashe (BASKARA : Journal of Business and Entrepreneurship, 2025)
This study focuses on 10 central Indonesian commercial banks listed on the Indonesian Stock Exchange from 2008 - 2022. Given Indonesia's significant economic growth and the crucial role of banks in its economy, we aim to explore the impact of key financial indicators - capital adequacy ratio, loan-to-deposit ratio, net interest margin, non - non-performing loan ratio, and net profit - on bank performance. By using descriptive and quantitative methods with secondary data, along with purposive sampling and panel data analysis via E- In views 10, we find novel results. Unlike previous studies, we discovered that capital adequacy and net profit profit negatively affect bank performance, while net interest margin has a positive impact. Additionally, the loan-to-deposit ratio and non-performing loan ratio show no significant effects. This challenges inconsistent findings and provides new insights for understanding bank performance in emerging economies like Indonesia, especially considering the unique economic events within the study period.